CORRELATION AND PATH CO-EFFICIENT ANALYSIS OF QUANTITATIVE AND QUALITATIVE TRAITS IN CHILLI (CAPSICUM ANNUUM L.) - SATISH KADWEY,; ASHWINI DADIGA,; SUNIL PRAJAPATI,; RAVI KUMAR TELUGU, (The Bioscan, 2015)
A field experiment was conducted during Rabi of 2012-13 at Vegetable Research Farm, Department of Horticulture, JNKVV, Jabalpur (M. P.). The experiment was laid out in Randomized Complete Block Design with 25 Chilli genotypes. The result express that seed yield plant -1 with dry fruit yield plant -1 (0.537), fruit yield plot -1 (0.368) and fruit yield ha -1 (0.368). Dry fruit yield plant -1 with green fruit yield plant -1 (0.573), fruit yield plot -1 (0.390) and fruit yield ha -1 (0.390) and fruit yield plot -1 expressed highly significant and positive correlation with fruit yield ha -1 (0.999). Highest positive direct effect viz., green fruit yield plant -1 showed fruit yield ha -1 (9.941), number of fruits plant -1 (0.366), plant height at 90 DAT (0.145), seed yield plant -1 (0.106), days to flower initiation (0.097), plant height at 60 DAT (0.095), dry fruit yield plant -1 (0.061), number of primary branches plant -1 at 30 DAT (0.056), number of primary branches plant -1 at 60 DAT (0.053). Whereas, the highest negative direct effect viz., green fruit yield plant -1 showed that fruit yield plot -1 (-9.914), plant height at 30 DAT ( 0.106), dry fruit weight (-0.090), plant height at 120 DAT (-0.085), fruit width (-0.049). Genotype US-611,-214, 947, 349,113, US-991, 2011/CHIVAR- 3,-4, 5, 9, 2012/CHIVAR-2, 3 had light green colour. US-214, 991, 2011/CHIVAR-2, 3, 4,5,6,7, 2011/CHIVAR- 8, 9, long fruits were observed among the genotypes.